2000
DOI: 10.1046/j.1523-1747.2000.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Amplification of the Human Plakophilin 1 Gene and Detection of a New Mutation in Ectodermal Dysplasia/Skin Fragility Syndrome

Abstract: Ectodermal dysplasia/skin fragility syndrome is a recently described autosomal recessive disease affecting skin, nails, and hair (MIM 604536), that results from mutations in plakophilin 1, a structural component of desmosomes. We report a new plakophilin 1 mutation in an affected patient as well as detailing the intron-exon organization of the gene to facilitate future polymerase chain reaction-based mutation screening. Using polymerase chain reaction amplification of genomic DNA, we identified 15 exons spanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
75
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 36 publications
(45 reference statements)
4
75
0
Order By: Relevance
“…Conversely, mutations in PKP1 result in ectodermal dysplasia/skin fragility syndrome characterized by skin, hair, and nail abnormalities but no cardiac phenotype. [22][23][24] Mutations in PKP2 were first described by Gerull et al 18 in a study that evaluated only 2 of a possible 32 kindreds with ARVC. Our study is the first to provide comprehensive clinical evaluation of ARVC families harboring mutations in PKP2.…”
Section: Syrris Et Al Pkp2 Mutations In Families With Arvcmentioning
confidence: 83%
“…Conversely, mutations in PKP1 result in ectodermal dysplasia/skin fragility syndrome characterized by skin, hair, and nail abnormalities but no cardiac phenotype. [22][23][24] Mutations in PKP2 were first described by Gerull et al 18 in a study that evaluated only 2 of a possible 32 kindreds with ARVC. Our study is the first to provide comprehensive clinical evaluation of ARVC families harboring mutations in PKP2.…”
Section: Syrris Et Al Pkp2 Mutations In Families With Arvcmentioning
confidence: 83%
“…Eight previous individuals with this disorder have been reported. [1][2][3][4][5][6][7] Plakophilin is a structural component of desmosomes, cell-cell adhesion complexes found in stratified squamous epithelia, myocardium, meninges, and parts of lymph nodes. 8 It also is expressed as a nuclear protein in several other cell types that lack desmosomes.…”
mentioning
confidence: 99%
“…Although PKP1 had been identified previously as a desmosomal component (Kapprell et al, 1988;Hatzfeld et al, 1994;Heid et al, 1994), it was not until the correlation of its absence with a human skin fragility disease that the importance of plakophilins in desmosomal adhesion was recognised. To date, three patients displaying complete ablation of PKP1 (McGrath et al, 1997;McGrath et al, 1999;Whittock et al, 2000) have been reported. These naturally occurring mutations provide valuable resources for the investigation of human PKP1 function.…”
mentioning
confidence: 99%